Campylobacteriosis following immunosuppression for immune checkpoint inhibitor-related toxicity. Issue 2 (5th October 2020) - Lee, Karla A; Shaw, Heather; Bataille, Véronique; Nathan, Paul
Abstract : Five patients receiving checkpoint inhibitor immunotherapy (CPI) under our care across two cancer centers over a 12-month period have subsequently developed campylobacterosis. All had received immune-suppressive treatment for CPI-related colitis in the weeks or months preceding the detection of Campylobacter infection, with negative stool cultures at presentation of CPI-related colitis. The immune-suppression required to treat CPI-related toxicity may lead to an increased risk of enteric infection within the gut. While the underlying immune and biologic mechanisms are not well understood, perturbation of the gut microbiota is an increasingly recognized factor capable of influencing CPI-mediated immune reconstitution and response to therapy. Clinicians should be aware that worsening of colitic symptoms in patients with a history of treatment for CPI-related colitis may be due to enteric infection, and not simply a relapse/deterioration of a previously treated CPI-related colitis. Judicious infectious disease evaluation is necessary for patients receiving CPIs as symptoms can mimic immune-related adverse events (irAEs). Furthermore, the benefits of immune-suppressive therapy for the treatment of presumptive irAEs must be weighed against the possible increased risk for either enteric infection or opportunistic infection. Prospective studies are required to investigate microbiome perturbations, resulting from immune-suppression, and guide future treatment of this patient cohort.